MENA Monitor : Economic Pressures Mount - Ianchovichina, Elena (World Bank, Washington, DC, 2014)
In 2013, Middle East and North Africa (MENA) regional growth is expected to slow to 3.8 percent from 6.1 percent in 2012. Growth deceleration into 2013 reflects a return to more sustainable growth in oil exporting countries, which reached 7.4 percent in 2012. Egypt's growth is expected to weaken relative to 2012, but in other oil importing countries economic activity is expected to expand faster than in 2012. This outlook is subject to a variety of risks. Political instability, policy uncertainty, and weakened macroeconomic fundamentals are the key challenges facing developing MENA countries. Slow growth in Europe poses additional problems, especially for Morocco and Tunisia.